Induction of the pro-myelocytic leukaemia gene by type I and type II interferons. Issue 5 (1998) - Heuser, M.; van der Kuip, H.; Falini, B.; Peschel, C.; Huber, C.; Fischer, T.
Abstract : The physiological role of the pro-myelocytic leukaemia (PML) gene product is poorly defined. Among other functions, PML is involved in haem atopoietic differentiation and in control of cell growth and tumorigenesis. We investigated the regulation of human PML expression by interferons (IFNs) and IL-1 in various human haematopoietic lines (U937, THP1, HL60, NB4), in human diploid fibroblasts and in human peripheral blood leukocytes. Cytokineinduced modulation of PML expression was assessed by Northern blot analyses, flow cytometry studies and in situ immunolabelling. Our data show that IFNs and IL-1 upregulate PML transcript and protein expression in a time and dose-dependent manner. In situ immunolabelling revealed that upregulation of protein expression by IFN-α is a consequence of a marked increase in both the number and the intensity of the staining of so-called PML nuclear bodies. Our data suggest that stimulation of PML expression by interferons and IL-1 may account for upregulation of PMLproteins observed in inflammatory tissues and in proliferative states.